(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Context: In Quebec, 61% of new nurses begin their career with a college degree. New graduates begin their careers early in intensive care units (ICU). That said, most are poorly prepared to assume their role in a critical care unit since critical care is an advanced skill. In Quebec, a preceptorship program has been established by the Ministry of Health and Social Services to support novices during their transition. In Abitibi-Témiscamingue (Ab.-T.), a remote region of Quebec, ICU preceptors often state that they receive little support and report a lack of resources as well as a lack of content to address with their learners. Objectives: The main objective of this study was to develop a preceptorship program for ICU novice nurses, adapted to the reality of practice in Ab.-T., and assess its implementation. Methods: Guided by the skills acquisition model adapted from Dreyfus and Dreyfus (1980) by Benner (1984/2001) and Caffarella’s interactive program planning model (2002), four cycles of action research led to the development of a preceptorship program in collaboration with preceptors using focus groups and the literature review of two existing programs. Individual interviews were conducted with 14 nurses (five preceptors and nine novices from two ICUs in the region where the study took place) who participated in the implementation of the program, were processed by vertical thematic analysis, then transversal, and allowed the evaluation of the implementation of the program. Results: The participation of the preceptors led to the development of a preceptorship program and several complementary tools adapted to the reality of practice in Ab.-T. The key learning outcomes as perceived by the novices relate to the improvement of their interventions and their ability to carry out new ones, which testifies to the development of competencies in compliance with Benner’s model (1984/2001). The preceptors now state that they are better equipped to provide clinical support to novices. This study has shone a light on the satisfaction of participants regarding the program at hand, whose content is considered consistent with the reality of practice in remote regions. Conclusion: The development of this program made it possible to support the preceptors. As for novices, they now state that they are better prepared to respond to complex ICU care situations in remote regions. The results of this study may be of interest to hospitals located outside major cities wishing to establish or review the offer of preceptorship to their novice nurses in the ICU.